A Transcriptome-Wide Association Study Identifies Novel Candidate Susceptibility Genes for Pancreatic Cancer. (5th April 2020) - Zhong, Jun; Jermusyk, Ashley; Wu, Lang; Hoskins, Jason W; Collins, Irene; Mocci, Evelina; Zhang, Mingfeng; Song, Lei; Chung, Charles C; Zhang, Tongwu; Xiao, Wenming; Albanes, Demetrius; et al.
Abstract: Background: Although 20 pancreatic cancer susceptibility loci have been identified through genome-wide association studies in individuals of European ancestry, much of its heritability remains unexplained and the genes responsible largely unknown. Methods: To discover novel pancreatic cancer risk loci and possible causal genes, we performed a pancreatic cancer transcriptome-wide association study in Europeans using three approaches: FUSION, MetaXcan, and Summary-MulTiXcan. We integrated genome-wide association studies summary statistics from 9040 pancreatic cancer cases and 12 496 controls, with gene expression prediction models built using transcriptome data from histologically normal pancreatic tissue samples (NCI Laboratory of Translational Genomics [n = 95] and Genotype-Tissue Expression v7 [n = 174] datasets) and data from 48 different tissues (Genotype-Tissue Expression v7, n = 74–421 samples). Results: We identified 25 genes whose genetically predicted expression was statistically significantly associated with pancreatic cancer risk (false discovery rate < .05), including 14 candidate genes at 11 novel loci (1p36.12: CELA3B ; 9q31.1: SMC2, SMC2-AS1 ; 10q23.31: RP11-80H5.9 ; 12q13.13: SMUG1 ; 14q32.33: BTBD6 ; 15q23: HEXA ; 15q26.1: RCCD1 ; 17q12: PNMT, CDK12, PGAP3 ; 17q22: SUPT4H1 ; 18q11.22: RP11-888D10.3 ; and 19p13.11: PGPEP1 ) and 11 at six known risk loci (5p15.33: TERT, CLPTM1L, ZDHHC11B ; 7p14.1: INHBA ; 9q34.2: ABO ; 13q12.2: PDX1 ; 13q22.1: KLF5; and 16q23.1: WDR59, CFDP1, BCAR1, TMEM170A ). The association for 12 of these genes ( CELA3B, SMC2, and PNMT at novel risk loci and TERT, CLPTM1L, INHBA, ABO, PDX1, KLF5, WDR59, CFDP1, and BCAR1 at known loci) remained statistically significant after Bonferroni correction. Conclusions: By integrating gene expression and genotype data, we identified novel pancreatic cancer risk loci and candidate functional genes that warrant further investigation.